A comparative study on cyber ethics, religious awareness and satisfaction in using Facebook for social networking - Hashim, Che Noraini; Syed Hassan, Sharifah Sariah (MCSER Publishing, Rome-Italy, 2013)
Throughout the internet’s evolution , debates on cyber ethics had raised concerns within the educational system. New ethical dilemmas turned to emerge out of compounding facebook communication among users. Ethical behaviour involving computer networking has immense power in promoting not only valuable academic networking, but could be shifted for self-fulfillment and even for evil ends. The issue of moral behavior involving computer networking is defined as cyber ethics. Arief, Dana, and Aniati (2011) synthesized the definition of ethics as right or wrong behavior based on respect. Studies relating to moral values further, systemize, defend and recommend concepts of right and wrong behavior. Despite the arguments of ethics as guidelines of social behavior and reflections of morality, Kaddu (2007) conceptualizes ethics as a set of values that lead to happiness, success and fulfillment. Guarded with some religious awareness, will cyber ethics makes a difference across boundaries and could religious values guide usage satisfaction during Facebook communication? This paper aims to clear doubts on cyber ethics using samples drawn from Facebook social communication among Malaysian and Indonesian undergraduates. It shall identify patterns of relationship between cyber ethics, religious awareness and usage satisfaction. The paper also discusses some implications of these relationships to reveal the level of satisfaction in using Facebook.Questionnaires were distributed to selected universities from Indonesia and Malaysia; 200 undergraduates responded. Correlation, independent t-test and multiple regression analysis were conducted on the data set. The measurement level such as honesty, truthfulness and respect were applied. The study revealed that cyber ethics across boundaries was significantly different. There is a significant relationship between religious awareness and cyber ethics. Facebook communication in the two countries was used by respondents with some religious awareness. This relationship has significant influence on the level of satisfaction while communicating in social networking sites.